Colored dual-functional photovoltaic cells. (13th April 2016) - Lee, Kyu-Tae; Lee, Jae Yong; Xu, Ting; Park, Hui Joon; Guo, L Jay
Abstract: In this article, we review our recent efforts on multi-functional photovoltaic (PV) cells that can produce desired reflective, transmissive, or neutral colors, by controlling light interaction with semiconductors and electrode structures in a desired manner. The PV cells integrated with plasmonic color filtering schemes using subwavelength gratings, and other approaches exploiting photonic resonances in an optical nanocavity consisting of highly absorbing semiconductor media are described. For further enhancement of optical and electrical performance characteristics of the multi-functional PV cells, possible difficulties and the outlook for future work are discussed.